Off the conservation radar: the hidden story of Europe's tiny pea clams (Bivalvia: Sphaeriidae) - Dariusz Halabowski; Ronaldo Sousa; Manuel Lopes-Lima; Ian Killeen; David C Aldridge; Katarzyna Zając; Jon Hamner Mageroy; Daniel Alan Cossey; Maria Urbańska; Martin Österling; Vincent Prié (Biodiversity and Conservation, 2024)
This study highlights the conservation problems faced by the tiny freshwater bivalves of the family Sphaeriidae, also known as pea, pill, or fingernail clams (or mussels) in Europe. Despite their global distribution, assumed ecological importance, and potential uses, basic knowledge about their taxonomy, biology, and ecology is very limited and much lower than for the larger freshwater bivalve taxa. Immediate scientific priorities are required to fill knowledge gaps regarding their taxonomy, genetic diversity, distribution, reproductive cycle, ecosystem functions, and population trends. Such fundamental knowledge is necessary to identify specific threats and develop appropriate conservation actions. Deploying environmental DNA analysis at a large scale could be a valuable way to fill gaps in distribution and strengthen monitoring in areas where local taxonomic knowledge is lacking. Until taxon-specific management plans can be developed, we recommend that efforts concentrate on the general protection and restoration of wetland habitats, implementing pollution control measures, and managing invasive species. These actions should be complemented by community engagement through citizen science initiatives. Additionally, prioritising data collection to fill existing knowledge gaps and updating conservation statuses (Red Lists) based on comprehensive assessments will be crucial. Implementing these actions will provide a starting point for the broader protection of freshwater ecosystems, thus benefiting pea clams and other interconnected species within these habitats.